THE IMPACT OF EMOTIONAL INTELLIGENCE ON WORKPLACE PERFORMANCE: A CROSS-CULTURAL STUDY - Hina Raza (Global Journal of Multidisciplinary and Applied Sciences, 2024)
Emotional intelligence (EI) refers to the ability to recognize, understand, manage, and influence emotions in oneself and others. In the workplace, EI has been linked to improved interpersonal relations, leadership capabilities, and overall performance. This study explores the impact of emotional intelligence on workplace performance through a cross-cultural lens, focusing on Pakistan and comparing it to global perspectives. The research aims to examine how emotional intelligence affects various aspects of workplace performance, such as job satisfaction, productivity, team collaboration, and leadership effectiveness. Through surveys and interviews conducted with employees in both Pakistani and international contexts, the study highlights cultural differences in emotional intelligence perceptions and its role in enhancing professional outcomes. The findings suggest that while EI is universally important, its influence varies depending on cultural values, communication styles, and organizational practices. The article concludes by offering recommendations for integrating emotional intelligence training into organizational development programs to enhance workplace performance globally.